C(sp3)–H oxidation and chlorination catalysed by a bioinspired pincer iron(iii) complex. Issue 31 (27th July 2022) - Han, Jian; Tan, Liming; Wan, Yanjun; Li, Gang; Anderson, Stephen N.
Abstract : A pincer iron(iii ) catalyst for the oxidation and chlorination of C(sp 3 )–H bonds was developed. Abstract : A pincer iron(iii ) catalyst for the oxidation and chlorination of C(sp 3 )–H bonds was developed. Oxidation of a diagnostic substrate cis -decalin implies that a long-lived carbon-centred radical is involved. Mechanistic studies suggest that an Fe-oxo species could be responsible for the rate-determining C–H activation step. This report expands the scope of non-heme catalysts for C–H functionalisation.